Effects of moisture content, temperature and pollutant mixture on atmospheric corrosion of copper and silver and implications for the environmental design of data centers (RP-1755). (20th April 2020) - Zhang, Rui; Zhang, Jianshun; Schmidt, Roger; Gilbert, Jeremy; Guo, Beverly
Abstract : The effects of moisture content, temperature and pollutant mixture on atmospheric corrosion of copper and silver were investigated by exposing test specimens to different environmental conditions, followed by surface characterization using the coulometric reduction, Scanning Electron Microscopy and Energy Dispersive Spectrometry (SEM/EDS). Printed circuit board test cards (PCBs) with bare copper were also used to investigate the effects of voltage bias on the PCBs on the corrosion rate. The test specimens were exposed to mixed flowing gases (MFG) environment with 8 different combinations of the following five pollutants at the fixed concentration levels: 60 ppb O3, 80 ppb NO2, 40 ppb SO2, 2 ppb Cl2 and 10 ppb H2 S. Temperature and relative humidity were varied from a reference condition (21 0 C and 50% RH which is within the current ASHRAE-recommended thermal envelope) to a higher value (28 ° C, 70% RH or 80% RH) to effect the moisture content of the test environment. The test results revealed the dominating effect of Cl2 on copper corrosion and that of H2 S on silver corrosion. Increasing the moisture content at 21 ° C caused more severe corrosion for copper when Cl2 was present, but not for silver. When temperature was increased from 21 ° C to 28 ° C at 50% RH, it reduced the corrosion on copper, but not on silver. Voltage biased PCBs had a less effect on corrosion than PCBs without the bias. These results could be used for possible expansion of the ASHRAE-recommended thermal envelope for data centers when Cl2 and H2 S are not present, and limit the thermal envelope when Cl2 or H2 S are present.